Bioequivalence and Bioavailability Studies: Regulatory Assessment and Study Design Considerations and Pharmacokinetic Parameters - Bhalerao, Atharva Surendra; Sonawane, Sandeep (Indian Journal of Pharmaceutical Education and Research)
Bioequivalence and bioavailability studies are vital components of the pharmaceutical industry, ensuring the safety, efficacy and interchangeability of generic drugs compared to their reference products. This comprehensive research paper dives deeper into the concepts of the principles of bioequivalence and bioavailability. The application of the Biopharmaceutics Classification System (BCS) in evaluating bioequivalence, different study designs used in these assessments. A thorough review of bioequivalence evaluation in line with guidelines from the US Food and Drug Administration (USFDA) and the European Medicines Agency (EMA).
Keywords: Bioequivalence; Study Design; EMA; USFDA.